A higher Mediterranean diet score, including unprocessed red meat, is associated with reduced risk of central nervous system demyelination in a case-control study of Australian adults - Black, LJ; Baker, K; Ponsonby, A-L; van Der Mei, I; Lucas, RM; Pereira, G; Ausimmune Investigator Group (Oxford University Press, 2019)
Background The evidence associating diet and risk of multiple sclerosis (MS) is inconclusive.